2012
DOI: 10.1039/c1fo10166h
|View full text |Cite
|
Sign up to set email alerts
|

(−)-Secoisolariciresinol attenuates high-fat diet-induced obesity in C57BL/6 mice

Abstract: Flaxseed lignan, secoisolariciresinol has been reported to possess health benefits. We previously synthesized each stereoisomer of secoisolariciresinol and found that (-)-secoisolariciresinol reduces lipid accumulation and induces adiponectin production in 3T3-L1 adipocytes. Here we show the effects of (-)-secoisolariciresinol on high-fat diet-induced obesity in C57BL/6 male mice. Oral administration of (-)-secoisolariciresinol for 28 consecutive days significantly suppressed the gain of body weight. Increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 21 publications
(21 reference statements)
2
6
0
Order By: Relevance
“…Flaxseeds contain ~ 30% dietary fibers, consumption of which has been shown to reduce fat digestibility and body weight gain in rats [38]. In addition, flaxseed lignan secoisolariciresinol diglucoside exerts a suppressive effect on body weight gain in mice by altering lipid metabolism [39]. Our result is in line with the effect of flaxseed on body weight gain reported earlier in rodents.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Flaxseeds contain ~ 30% dietary fibers, consumption of which has been shown to reduce fat digestibility and body weight gain in rats [38]. In addition, flaxseed lignan secoisolariciresinol diglucoside exerts a suppressive effect on body weight gain in mice by altering lipid metabolism [39]. Our result is in line with the effect of flaxseed on body weight gain reported earlier in rodents.…”
Section: Discussionsupporting
confidence: 88%
“…This suggest that even though initially the flaxseed group mice were reluctant to eat the fortified diet, they became accustomed to it and consumed it as well as the control diet during the majority of the study. The flaxseed-fed mice had lower average body weight at the end of the study which could be attributed to, (i) reduced food consumption in the first two months of the study, (ii) reduced fat digestibility [38], and/or (iii) altered adipogenesis-gene regulation [39]. The decrease in average weight of lungs in the flaxseed fed mice as compared to control group mice suggest tumor burden may be a contributing factor.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, high‐fat diet‐induced visceral and liver fat accumulation was significantly reduced by administration of SDG to mice . SECO might reduce lipid accumulation by changing the expression of various genes related to the synthesis and β ‐oxidation of fatty acids . In our study, a negative correlation was observed between the visceral fat per final body weight and the urinary amounts of SECO of the two groups ( r = −0.54).…”
Section: Discussionsupporting
confidence: 48%
“…Obese C57N mice showed also lower levels of enterolactone in cecum. Subcutaneous injection of enterolactone and enteridiol tend to decrease body weight in mice (Tominaga et al, 2012). The patterns of urobilinoids are likely due to different communities that were observed in C57J and C57N mice by our 16S-rRNA gene analyses.…”
Section: Discussionmentioning
confidence: 78%